Stress and job performance of public secondary school teachers - Felisarta, Willam M. (Southeastern Philippines Journal of Research and Development, 2014)
The study investigated the extent of stress and the level of job performance of public school teachers of Tagum City division. A descriptive-correlational research design was used to determine the relationship between the extent of stress and the level of job performance of teachers. There were 391 respondents and complete enumeration sampling technique was used in determining the population. Results revealed that (1) there was a significant difference on the extent of stress experience by the teacher when analyzed according to gender; (2) there was no significant difference on the level of performance of teachers when analyzed according to gender; (3) the extent of stress of teacher was experienced in some occasions; (4) there was no significant relationship between the extent of stress and the level of performance of teachers; (5) the level of job performance of teachers yielded a very satisfactory result; and (6) the computed r-value of -0.223 indicates a negligible negative correlation while the computed t-value of 1.209 is lesser than the tabulated t-value of 2.048, thus, the null hypothesis is accepted.